Creative Accounting: Viewed from Risk and Sharia Compliance Perspective - Muhammad Noor; Sopian Sopian (Journal of Islamic Economic Laws, 2023)
Company with a corporate form which is a result of the industrial revolution rises a principal and agent relationship. The separation between company’s owner and people who run the company makes accounting needs become more crucial. However, accounting which is a solution for communication between owners and management is often exploited by managers through creative accounting, also known as earnings management. This study aims to determine the effect of firm risk, tax risk, and sharia compliance on earnings management. The research was conducted on manufacturing sector companies listed on Indonesia Stock Exchange (IDX) in 2016-2019. Using purposive sampling method, the number of samples used is 69 companies with a total of 276 observations. The hypothesis examination used in this research is multiple linear regression analysis of pooled data. The result show that firm risk from the perspective of debtholders has a positive effect on earnings management. As for firm risk from equity holders’ perspective, tax risk, and sharia compliance has no effect on earnings management.